ArchiCAD 19--the definitive guide : dive into the wonderful world of building information modeling (BIM) to become a productive ArchiCAD user /: dive into the wonderful world of building information modeling (BIM) to become a productive ArchiCAD user. (2015) - MacKenzie, Scott H; Rendek, Adam
No abstract available